Islamic Value-Based Quality Management:Evaluation and Implementation Strategy for Globally Competitive Education - Asykur, Muamar; Amri, Amri; Ramlianto, Ramlianto; Lukman, M. (International Journal on Advanced Science, Education, and Religion, 2025)
This article discusses the concept of Islamic value-based quality management, evaluation strategies, and implementation in globally competitive education. By combining Islamic principles such as ihsan (perfection) and shura (deliberation), and the Total Quality Management (TQM) approach, this article offers a guide to improving the quality of education and achieving global excellence. The results of the study indicate that the application of Islamic values ​​in educational quality management can improve the quality of education and student competence in facing global challenges.Quality management in Islamic education is more popularly known as Total Quality Management (integrated quality). In the implementation of Islamic education quality management, there are several things that must be considered: Continuous Improvement, Setting Quality Standards, Changing Organizations. Quality improvement must be carried out comprehensively based on the size, level, provisions and assessment of the quality of goods or services (products) according to customer satisfaction. This utilization is carried out through effective, efficient and productive cooperation to achieve happiness and prosperity both in the world and in the hereafter.